Starting & running a sandwich-coffee bar : an insider guide to setting up your own successful business / Stephen Miller - Miller, Stephen
At the age of 42, former lawyer Stephen Miller opted for a career change and set up his own sandwich-coffee bar. Despite the challenges and hard work, he has found it very satisfying to set up and run his own business. He shares his advice and experience in this book.